Ефективність зонування і оптимізація функціонування насосних установок систем гарячого водопостачання будівель - Абєлєшов, В. І. (НТУ "ХПІ", 2010)
Робота присвячена розгляду деяких питань економії енергії шляхом підвищення ефективності зонування і оптимізації функціонування насосних установок систем гарячого водопостачання житлових будівель, готелів і туристичних комплексів.

Work is devoted to consideration of some questions of economy of energy by the increase of efficiency of zones division and optimization of functioning of pumps setting of the systems of hot water-supply of dwelling-house, hotels and tourist complexes.
Efficiency of zones division and optimization of functioning of pumps setting of the systems of hot water-supply of buildings
Keywords: енергія; зонування; насосні установки; водопостачання